2020
DOI: 10.3390/ijerph17124254
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Sedentary Behaviour Patterns among Kenyan and Japanese Children: A Comprehensive Cross-Country Comparison

Abstract: Health benefits of physical activity are well known, yet available physical activity data is limited from children living in African and Asian countries. The purpose of the cross-sectional study was to evaluate and compare physical activity and sedentary behavior patterns, particularly hourly variations, among children in Kenya and Japan. Participants included 298 primary school students (122 Kenyan, 176 Japanese) aged 9–12 years. Physical activity and sedentary behavior were measured with accelerometers. Doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…At ages 14 and 15 years, the gap in SB between our cohort (511 min/day) and the cohort reported by Mitchell et al (492 min/day) was considerably narrower. However, our results were comparable to other current studies as they did not reflect a higher level of SB time among school-aged children 20 , 21 .…”
Section: Discussionsupporting
confidence: 87%
“…At ages 14 and 15 years, the gap in SB between our cohort (511 min/day) and the cohort reported by Mitchell et al (492 min/day) was considerably narrower. However, our results were comparable to other current studies as they did not reflect a higher level of SB time among school-aged children 20 , 21 .…”
Section: Discussionsupporting
confidence: 87%
“…Our findings revealed that all Maasai children met this guideline, which far exceeds Nairobi boys (77.8%) and Nairobi girls (75.0%). In addition, compared to previous studies using the same accelerometer (ActiGraph), the Maasai children also showed higher MVPA than children from other countries including Europe (Steene-Johannessen et al, 2020), UK (Brazendale et al, 2021), United States (Brazendale et al, 2021), Australia (Brazendale et al, 2021), Brazil (Brazendale et al, 2021), Japan (Kidokoro et al, 2020), and Mozambique (Manyanga et al, 2019). Additionally, Maasai children demonstrated significantly higher weekend MVPA than Nairobi children.…”
Section: Discussionmentioning
confidence: 48%
“…Active school transport was assessed by a questionnaire that was used in previous international comparison studies (Gropp et al, 2013;Kidokoro et al, 2020;Sarmiento et al, 2015). The participants were asked about the main mode of transport they used to go to school during the last week.…”
Section: Active School Transportmentioning
confidence: 99%
“…This observation might indicate that urbanization and the changing life styles increase sex differences in PA. Adebusoye et al [( 49 ), p. 554] argued that urban development in Africa might reduce the number of conducive spaces for outdoor PA, which might be even less accessible for girls. Given that the highest population growth (and especially growth in urban areas) is expected over the next few decades in Africa and Asia ( 50 ), it is important to understand the factors that influence children's PA behaviors in these regions to create effective interventions to prevent a decline in PA ( 51 ). In this respect, in urbanized settings, girls constitute a special target group as they are more likely to engage in insufficient MVPA.…”
Section: Discussionmentioning
confidence: 99%